Guidelines for the management of diabetic macular edema by the European Society of Retina Specialists (EURETINA) - Schmidt-Erfurth, Ursula; Jonas, Jost B. (Ophthalmologica, 2017)
Diabetic retinal disease is envisioned to become the plague of the coming decades with a steep increase of worldwide diabetes incidence followed by a substantial rise in retinal disease. Improvements in diagnostic and therapeutic care have to cope with this dilemma in a clinically and socioeconomically efficient manner. Laser treatment has found a less destructive competitor in pharmacological treatments. As a consequence of recent rigorous clinical trials, laser photocoagulation is no longer recommended for the treatment of diabetic macular edema (DME), and anti-vascular endothelial growth factor therapy has emerged as first-line therapy. Steroids have maintained a role in the management of chronically persistent DME. The paradigm shifts in therapy are accompanied by a substantial break-through in diagnostics. The following guidance for the management of DME has been composed from the best updated knowledge of leading experts in Europe and represents another volume in the series of EURETINA recommendations for the management of retinal disease.
Gesehen am 26.04.2018